ERROR ANALYSIS: WRITING ENGLISH FOR TOURISM BY STUDENTS' PRIVATE UNIVERSITY IN LANDAK REGENCY IN ACADEMIC YEARS 2025-2026 - Tuminah; Sala, Alberta Ranisa; Rio, Is Sandra (JR-ELT (Journal of Research in English Language Teaching), 2025)
Language is an essential part of human life as it serves as a means of communication. Every country uses its own language. Language also requires skills, one of which is the ability to write in the English language. The aim of this study is to identify the types of errors made by students when writing sentences in English in the context of tourism, as well as to determine the most common errors made by students when writing English sentences related to tourism. Students express their ideas and thoughts, including English texts about tourism. When writing English texts on tourism, students often make mistakes in using the present simple, past simple, and future simple tenses. These errors are particularly related to the taxonomy structure, where mistakes are made in grammar and sentence structure in the target language (English), such as addition, omission, misinformation, and misordering. This study aims to identify the types of errors that occur when using the present simple, past simple, and future tenses in writing English texts about tourism. The researcher used a qualitative descriptive approach for documentation and data analysis. The researcher found four types of errors: misinformation, omission, misordering, and addition. In terms of error frequency, omission errors were the most common, occurring in 69% of cases, followed by ignorance errors at 56%, addition errors at 44%, and misordering errors, which occurred the least at 0.